Princess of glass - George, Jessica Day, 1976- (Bloomsbury U.S.A. Children's Books, 2010)
In the midst of maneuverings to create political alliances through marriage, sixteen-year-old Poppy, one of the infamous twelve dancing princesses, becomes the target of a vengeful witch while Prince Christian tries to save her.